157 An insight into implanters' practices of ICD implantation: a physician survey. (9th June 2011) - Sadarmin, P P; Wong, K C K; Rajappan, K; Bashir, Y; Betts, T R
Abstract : Introduction: The Implantable cardioverter defibrillator (ICD) is the mainstay of treatment for the prevention of sudden cardiac death (SCD) and the management of tachyarrhythmias. Informed patient consent is an essential part of the implant process. Our aim was to get an insight into implanters' (Imp) practices prior to an ICD implantation. Methods: A questionnaire survey was sent to UK ICD Imp to test their knowledge of the risk and benefits of an ICD in patients who satisfy trial and national guideline criteria and the incidence of implant complications. Information of the style and language of consent was requested. This questionnaire was specifically aimed at Imp and was part of the larger questionnaire looking at knowledge, attitudes and factors influencing ICD prescription in the UK. Results: Replies were received from 23 implanters. 35% of the responders were between the age of 30–39 years and 39% were between 40 and 49 years. 83% of the responders were Consultants and 96% were working in an implantating centre. 83% of Imp were fully aware of Primary Prevention (PP) NICE guidelines while 78% were fully aware of Secondary Prevention (SP) NICE guidelines. There was widespread use of information leaflets (87%) and specialist ICD nurses (83%) to disseminate information to patients. All responders said they would personally discuss the therapy with the patient prior to the implantation regardless of the referral source. A discussion regarding the prevention of SCD, inappropriate shocks and driving restrictions were performed by 96% of responders and device infections and lead failures discussed by 91%. Use of absolute risk reduction in percentages and number needed to treat while explaining the risks and benefits gained from ICDs were used by 22% and 26% respectively. There was widespread use of phrases like "small risk" or "moderate risk" (61%) and life prolongation (eg, lets you live longer by an average of 3 months) (30%). Replies also indicated that Imp under-estimate overall mortality in medicallytreated and ICD-treated patients, lead dislodgement requiring re-positioning and major haematoma requiring reoperation. Imp overestimate infections leading to device removal and the incidence of pneumothorax when compared to published trial or study data. Conclusion: The majority of implanters are aware of UK ICD guidelines. The patient consent process is not universal. Guidelines and awareness about end-of-life care in ICD patients is needed and should be part of the initial consent process. Evidence based use of risk and benefit terminologies like ARR and NNT are needed to better inform the patient rather than abstract phrases. Increasing awareness of ICD complication rates can help patients and physicians balance risk against benefit which could lead to improved patient satisfaction with their therapy.